Versatility of Bi- Paddle PMMC Flap in Reconstruction of Oral Facial Defects - Hemanth Nagavarma, Prakash B V1 , Mohammed Zuhaib2 , (International Journal of Scientific Research and Management (IJSRM), 2017)
Pectoralis major myocutaneous (PMMC) flap continues to be the workhorse in head and neck reconstruction. Although free tissue transfer has revolutionized the reconstruction in cancers of the oral region. The objective of this study was to assess the versatility of pectoralis major myocutaneous (PMMC) flap in the reconstruction of diverse surgical defects following resection. Ariyanhas first reported the use of PMMC in 1979 for reconstruction of Head and Neck Defects